2016
DOI: 10.1159/000446429
|View full text |Cite
|
Sign up to set email alerts
|

Methadone-Related Overdose Deaths in a Liberal Opioid Maintenance Treatment Programme

Abstract: Background/Aims: Increasing rates of overdose deaths involving opioid maintenance treatment (OMT) medications and particularly methadone have been observed concurrently with the implementation of liberal OMT strategies (i.e. minimum of control and high doses prescribed). This study examined methadone-related overdose deaths in a liberal OMT programme. Methods: Drug-overdose deaths (n = 130) with detection of methadone in Copenhagen, Aarhus, and Odense Municipality, Denmark, during the period 2008-2011 were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
3
32
1
Order By: Relevance
“…Prior to the introduction of the patient choice reform, a concern was raised that an expansion of the number of patients in treatment, and thus an increase in individuals receiving medication in the form of methadone and buprenorphine, could lead to increased diversion of these medications to people not in OST. This is something that has been observed in other studies where access to OST has increased [17,18,27,30,50,51]. The analyses in this study show that there was no signi cant increase in deaths caused by methadone or buprenorphine in general in Skåne between periods examined.…”
Section: Discussionsupporting
confidence: 85%
“…Prior to the introduction of the patient choice reform, a concern was raised that an expansion of the number of patients in treatment, and thus an increase in individuals receiving medication in the form of methadone and buprenorphine, could lead to increased diversion of these medications to people not in OST. This is something that has been observed in other studies where access to OST has increased [17,18,27,30,50,51]. The analyses in this study show that there was no signi cant increase in deaths caused by methadone or buprenorphine in general in Skåne between periods examined.…”
Section: Discussionsupporting
confidence: 85%
“…Pharmacotherapy for OUD is a well-established component of treatment (Ries et al, 2009) and many studies have shown an association between OUD pharmacotherapy and mortality (Cornish et al, 2010; Degenhardt et al, 2009; Pierce et al, 2016). The lack of association in this population may be due to differences between this and other populations studied, the nature of the services they were receiving, or because of the well-documented increased risk of mortality during times of pharmacotherapy treatment initiation and cessation (Buster et al, 2002; Cornish et al, 2010; Cousins et al, 2016; Degenhardt et al, 2009; Kimber et al, 2015; Pierce et al, 2016; Pierce et al, 2015; Tjagvad et al, 2016). This is also an observational study and causal inferences cannot be made.…”
Section: Discussionmentioning
confidence: 83%
“…[43][44][45] Regarding adverse events, only a minor effect on corrected QT (QTc) interval duration has been reported with therapeutic doses of buprenorphine-naloxone, without proarrhythmic effects. 46,47 Conversely, methadone can increase the risk of a rare but fatal ventricular arrhythmia (torsades de pointes) because of its substantial QT-prolonging effects, especially at higher doses.…”
Section: Disadvantagesmentioning
confidence: 99%